2019
DOI: 10.1111/jvim.15476
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical dilation, botulinum toxin A injection, and surgical myotomy with fundoplication for treatment of lower esophageal sphincter achalasia‐like syndrome in dogs

Abstract: Background Megaesophagus (ME) carries a poor long‐term prognosis in dogs. In people, lower esophageal sphincter (LES) achalasia is a rare cause of ME that may respond to targeted intervention. Dogs with lower esophageal sphincter achalasia‐like syndrome (LES‐AS) have been described recently, warranting investigation of analogous targeted treatment. Hypothesis/Objectives Evaluate response of dogs with LES‐AS to LES mechanical dilation and botulinum toxin A (BTA) injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 47 publications
0
41
0
Order By: Relevance
“…Retention of ingesta within the oesophagus was seen commonly in dogs within this study and is presumed to occur in many dogs with ME. This retention could be presumed to lead to the development of esophagitis, and oesophageal mucosal changes have been noted during endoscopy of dogs with ME (Grobman, Hutcheson, et al., 2019). For this reason, many owners of dogs in this study were advised to administer an oral proton pump inhibitor (omeprazole).…”
Section: Discussionmentioning
confidence: 99%
“…Retention of ingesta within the oesophagus was seen commonly in dogs within this study and is presumed to occur in many dogs with ME. This retention could be presumed to lead to the development of esophagitis, and oesophageal mucosal changes have been noted during endoscopy of dogs with ME (Grobman, Hutcheson, et al., 2019). For this reason, many owners of dogs in this study were advised to administer an oral proton pump inhibitor (omeprazole).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, AeroD may present in the absence of GI clinical signs (CS) and with normal thoracic radiographs making clinical recognition challenging 2 . Correction of the underlying AeroD has been demonstrated to improve clinical outcome, making identification of AeroD critical for optimal case management 6,9‐11 …”
Section: Introductionmentioning
confidence: 99%
“… 2 Correction of the underlying AeroD has been demonstrated to improve clinical outcome, making identification of AeroD critical for optimal case management. 6 , 9 , 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…This is especially important because our group later demonstrated that dogs with LES-AS, like people with LES-achalasia, respond to intervention directed at relieving the obstruction at the LES (Chapter 4). (313) In our study mechanical dilation and botulinum toxin A (BTA) injections at the LES resulted in 100% perceived clinical improvement by owners as well as significantly increased body weight, body condition score, and significantly reduced regurgitant frequency. (313) These subjective and objective clinical assessments were supported by improved swallowing parameters as detected by VFSS.…”
Section: Conclusion and Future Diretionsmentioning
confidence: 78%
“…A Heller myotomy with Dor fundoplication was found to be similarly effective and may represent a long-term intervention in dogs with LES-AS. (313) The findings of this study provide hope for a population of dogs with a disease for which there have been historically very few therapeutic options.…”
Section: Conclusion and Future Diretionsmentioning
confidence: 89%